Assessment of serological markers of dengue and it’s correlation to thrombocytopenia - Neha Goel; Ritika Kansal; Amit Joon; Jaya T. Hemnani (Tropical Journal of Pathology and Microbiology, 2020)
Background:Dengue is an acute, potentially fatal viral infection that can culminate in dengue hemorrhagic fever and dengue shock syndrome. The present study was conducted to assess the correlation between platelet counts and serological markers of dengue infection.Materials and Methods: The present study was conducted among 120 patients suspected of dengue fever. Serum samples were collected from suspected dengue fever patients. The samples were tested for NS1 antigen, IgM, and IgG antibodies using the ICT test kit. The platelet count was recorded in dengue parameter-positive and -negative cases.Results: Out of 120 patients, males were 70 and females were 50. NS1 only was detected in 62, IgM only in 20, IgG only in 14, NS1 and IgM only in 10, NS1 and IgG only in 8 and IgM and IgG only in 6 cases. 62 patients that were positive for NS 1, thrombocytopenia was seen in 48, 12 out of 20 IgM positive patients, 10 out of 14 IgG positive patients, 6 out of 10 NS1 and IgM only positive patients, 4 out of 8 NS1 and IgG only positive patients and 2 out of 6 IgM and IgG only positive patients were detected. The difference was significant (P< 0.05).Conclusion:In fever, thrombocytopenia is observed more uniformly in subjects positive for dengue. WheneverIgM is detected as compared to NS1 and can be used asan indicator to reduce the complication of dengue disease. The use of NS1 in the diagnosis of dengue increases the detection rate significantly.